Impacts of caring for a child with the CDKL5 disorder on parental wellbeing and family quality of life. Issue 1 (December 2017) - Mori, Yuka; Downs, Jenny; Wong, Kingsley; Anderson, Barbara; Epstein, Amy; Leonard, Helen
Abstract Background Although research in this area remains sparse, raising a child with some genetic disorders has been shown to adversely impact maternal health and family quality of life. The aim of this study was to investigate such impacts in families with a child with the CDKL5 disorder, a newly recognised genetic disorder causing severe neurodevelopmental impairments and refractory epilepsy. Methods Data were sourced from the International CDKL5 Disorder Database to which 192 families with a child with a pathogenicCDKL5 mutation had provided data by January 2016. The Short Form 12 Health Survey Version 2, yielding a Physical Component Summary and a Mental Component Summary score, was used to measure primary caregiver's wellbeing. The Beach Center Family Quality of Life Scale was used to measure family quality of life. Linear regression analyses were used to investigate relationships between child and family factors and the various subscale scores. Results The median (range) age of the primary caregivers was 37.0 (24.6–63.7) years and of the children was 5.2 (0.2–34.1) years. The mean (SD) physical and mental component scores were 53.7 (8.6) and 41.9 (11.6), respectively. In mothers aged 25–54 years the mean mental but not the physical component score was lower than population norms. After covariate adjustment, caregivers with a tube-fed child had lower mean physical but higher mean mental component scores than those whose child fed orally (coefficient = −4.80 and 6.79;p  = 0.009 and 0.012, respectively). Child sleep disturbances and financial hardship were negatively associated with the mental component score. The mean (SD) Beach Center Family Quality of Life score was 4.06 (0.66) and those who had used respite services had lower scores than those who had not across the subscales. Conclusions Emotional wellbeing was considerably impaired in this caregiver population, and was particularly associated with increased severity of child sleep problems and family financial difficulties. Family quality of life was generally rated lowest in those using respite care extensively, suggesting that these families may be more burdened by daily caregiving.